1984
DOI: 10.1002/eji.1830141212
|View full text |Cite
|
Sign up to set email alerts
|

Isotypes and specificities of immunoglobulins produced by germ‐free mice fed chemically defined ultrafiltered “antigen‐free” diet

Abstract: The regulation of the "spontaneously" occurring ("background") Ig synthesis of mice has been studied by determining the numbers of IgM-, IgG- and IgA-secreting cells and a part of the IgM antibody-specificity repertoire in spleen, bone marrow (BM) and mesenteric lymph nodes (MLN) of conventional and "antigen-free" mice. These antigen-free mice were germ-free raised and fed an ultrafiltered solution of chemically defined low molecular weight nutrients, and thus devoid of exogenous antigenic stimulation. The sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
1

Year Published

1985
1985
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(113 citation statements)
references
References 14 publications
7
100
1
Order By: Relevance
“…In mice living in a sterile environment and consuming an ultrafiltered low Ag diet (germfree Agfree mice), IgM levels were nearly normal and the IgM repertoire showed a normal diversity. But levels of circulating IgG and IgA were profoundly depressed and peripheral lymph nodes and mucosal lymphoid tissue were smaller than in conventionally housed animals (31,32).…”
Section: The Igm and Igg Repertoire During Intrauterine Developmentmentioning
confidence: 80%
“…In mice living in a sterile environment and consuming an ultrafiltered low Ag diet (germfree Agfree mice), IgM levels were nearly normal and the IgM repertoire showed a normal diversity. But levels of circulating IgG and IgA were profoundly depressed and peripheral lymph nodes and mucosal lymphoid tissue were smaller than in conventionally housed animals (31,32).…”
Section: The Igm and Igg Repertoire During Intrauterine Developmentmentioning
confidence: 80%
“…For example, a recent report from Pasare and Medzhitov (25) has demonstrated that MyD88-deficient mice express normal serum IgA Abs (although IgA secretion in the gut had not been explored). Furthermore, contradictory results have been published regarding the reduction of serum IgM levels in naive MyD88-deficient mice or MyD88/TRIF doubledeficient mice (25,26), and natural Abs are still produced in germfree mice (27,28). It cannot formerly be excluded that formation and replenishment of the pool of natural Abs involves compensatory mechanisms other than TLR signaling or that TLRs can be triggered by endogenous ligands.…”
Section: Discussionmentioning
confidence: 99%
“…However, it remains a paradox that Abs reactive with self-constituents are found in abundance in normal sera. Such Abs are thought to arise naturally without exogenous Ag stimulation, as they are present in cord blood and in newborn humans and mice, as well as in mice housed in germ-free conditions and fed an Ag-free diet (15)(16)(17)(18). They are therefore referred to as natural autoantibodies (NAA).…”
mentioning
confidence: 99%